Factor analysis of the functioning of small business and its development prospects under sanctions - M. V. Antyushin; I. V. Guskova; N. E. Serebrovskaya (Путеводитель предпринимателя)
The problems, difficulties, as well as issues of entrepreneurship development in Russia are considered based on the analysis of the retrospective of small and medium enterprises (SME) development, errors in the field of economic development in the process of transformation of the Russian economy in different periods of its development, as well as in different phases of the economic cycle are identified.The article is devoted to the study of environmental factors affecting the development and functioning of SMEs. The article presents the results of a sociological survey of entrepreneurs and experts in the field of economics and management. The survey is aimed at determining the impact of the external environment on the development of entrepreneurship in Russia and the possibility of overcoming it.